PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN UNTUK MENCIPTAKAN UMKM TANGGUH TERTIB LAPORAN KEUANGAN PADA MAMAIN FOOD - Ferdiansyah Ferdiansyah; Dwi Septiani; Fitri Sagantha; Adi Martono; Sunarto Sunarto (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2021)
For UMKM, making financial reports neatly in accordance with standards is still something that is difficult to do. Therefore, we Pamulang University lecturers want to help assist in the preparation of financial reports for UMKM. In this service activity, we provide a solution for using an application for making financial reports for UMKM, namely SI-APIK, the goal is for UMKM to make it easier to make financial reports with this application that is easy to use and understand by UMKM actors who do not have basic education. accountancy. In addition, the availability of the application on mobile phones and through the website makes it easier for MSME actors to input their economic transactions. This community service involves UMKM Mamain Food Indonesia as the object of research. The method used in the training is a direct method of face-to-face and mentoring, namely by analyzing and problem solving. Financial accounting materials are presented with lectures, training, questions and answers, demonstrations, and case resolution. Furthermore, the recording process begins with examples of simple transactions that are usually carried out through the SI APIK application, an android application issued by Bank Indonesia. The results of financial literacy training and financial reporting assistance through this android-based application went well, and there was an increase in understanding of basic knowledge of financial records and an increased understanding of the operation of android-based financial applications. This is evidenced by the results of recording the financial statements of UMKM actors, namely Mamain Food Indonesia, using the SI APIK application, which is more neat and according to standards than before and UMKM actors, namely Mamain Food Indonesia, have been able to carry out financial records of business operations carried out through the SI APIK application. So it can be concluded that the application of the Android-based SI APIK financial application can improve the ability of UMKM Mamain Food Indonesia in compiling financial reporting according to standards so that it will be easier to get capital from financial institutions.